Framing of China country image in COVID-19 period: A comparative analysis of Sin Chew Daily and People’s Daily - Jin , Fangfang; Ahmad*, Abdul Latiff; Kadir, Shamsiah Abd (Journal of Ecohumanism, 2025)
The World Health Organization (WHO) declared the outbreak (COVID-19) is a pandemic on March 11, 2020. This study aims to explore how Sin Chew Daily and People’s Daily report China in this special period. Based on the five generic frames (Semetko &Valkenburg, 2000), the study identifies the news frames used by each newspaper. The findings present three topics of Sino-US political and diplomacy, international politics and diplomacy, and Special region politics are most frequency in politics news by two newspapers. For the COVID-19 news, they emphasized the news topics of China anti-epidemic measures and epidemic dynamics. In social news , they paid more attention to the Nature disaster and Eastern Airline Crash. Besides, the study also reveals that both newspapers predominantly use the conflict frame on political news, and the human-interest frame on social news. For COVID-19 news, People’s Daily mainly employs the governance and reassurance frames, while Sin Chew Daily prefer to use the science frame, followed by reassurance, fear and tension frames. Futhermore, the study also showed the extent and types of news coverage by two newspapers. This study emphasized Chinese and Malaysia-Chinese media, which provides new empirical materials for the research area of China’s media image.